2013
DOI: 10.1186/1471-2458-13-908
|View full text |Cite
|
Sign up to set email alerts
|

Immunization coverage and predictive factors for complete and age-appropriate vaccination among preschoolers in Athens, Greece: a cross- sectional study

Abstract: BackgroundIn Greece, several new childhood vaccines were introduced recently but were reimbursed gradually and at different time points. The aim of this study was to assess immunization coverage and identify factors influencing complete and age-appropriate vaccination among children attending public nurseries in the municipal district of Athens.MethodsA cross-sectional study, using stratified sampling was performed. Immunization history was obtained from vaccination booklets. Demographic and socioeconomic data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 28 publications
6
56
2
1
Order By: Relevance
“…Rates remained very high for all 4 doses, both for the general population and immigrant children. 13,14,20,21 Coverage with 3 DTP doses by 12 months (95.7%), a key WHO indicator, was similar to the estimated coverage for the European region of WHO in 2013. 22 Delay in completing 4 doses by 24 months, although lower than in 2012, is possibly due to the increased number of vaccines in the second year of life.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Rates remained very high for all 4 doses, both for the general population and immigrant children. 13,14,20,21 Coverage with 3 DTP doses by 12 months (95.7%), a key WHO indicator, was similar to the estimated coverage for the European region of WHO in 2013. 22 Delay in completing 4 doses by 24 months, although lower than in 2012, is possibly due to the increased number of vaccines in the second year of life.…”
Section: Discussionmentioning
confidence: 73%
“…1A), in concordance with local data and suboptimal coverage rates in other countries. 13,14,20,21,28,29 The delay is attributable to the overcrowded vaccination schedule in the first 6 months as well as the nonuniversal use of hexavalent vaccines. The use of combined vaccines has potential benefits, including reduced number of patient visits, fewer complications associated with multiple injections, decreased stocking and visit costs, and lowering the risk of delayed or missed vaccinations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research conducted in Greece revealed that IPV was best accepted by caregivers in countries by repeated strong, clear and simple messages regarding the effectiveness of the new vaccines for caregivers. 14 In our study one interesting finding was that a quarter among the participants had attended polio surveillance training workshop in last 2 years and participated in polio National Immunization days. Increasing experience and attending training were insignificantly associated with knowledge of doctors about Polio Vaccine.…”
Section: Discussionmentioning
confidence: 80%